(untitled) (Signos do Consumo, 2023)
This paper discusses the dress worn by Brazilian Julia Gama, runner-up of the 69th Miss Universe pageant, created by designer Michelly X, a transgender woman, in the context of the Costurando Sonhos initiative, which offers professional training to women victims of domestic violence, in Paraisópolis, São Paulo. The ephemeral nature of fashion culminates in a system of transitory meanings, in which the individual communicates with society and expresses their identity through clothes and products. We can apply McCraken’s trickle-up as an imperative for learning the socio-cultural context in which imitation and differentiation occur, since clothing has a strong communicational function.